2014
DOI: 10.1039/c4cp02628d
|View full text |Cite
|
Sign up to set email alerts
|

NMR and ESR relaxation in Nd- and Gd-doped LaPO4: towards the accurate determination of the doping concentration

Abstract: We present an original method based on the (31)P solid-state NMR relaxation to determine low concentrations (<1 at%) of paramagnetic ions in monazite LaPO4 crystals with a high accuracy (∼0.1 at%). NMR experiments under static and MAS (15 kHz) conditions show that the (31)P relaxation time T1 is strongly affected by the presence of paramagnetic ions in the vicinity of the phosphorus nuclei. A linear variation of 1/T1 as a function of Nd(3+) or Gd(3+) concentration is shown in the 0-10 at% range for a homogeneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 35 publications
7
33
1
Order By: Relevance
“…A very long T 1 is observed for LaPO 4 (1714 s, see Table I) as expected for this diamagnetic compound [14]. Our value differs from the one of 600 s published previously [21,83], probably due to the presence of different small quantities of impurity. EuPO 4 possesses a short T 1 of 210 ms being close to that of the paramagnetic GdPO 4 (460 ms) [21].…”
Section: Longitudinal Relaxation Timessupporting
confidence: 57%
See 2 more Smart Citations
“…A very long T 1 is observed for LaPO 4 (1714 s, see Table I) as expected for this diamagnetic compound [14]. Our value differs from the one of 600 s published previously [21,83], probably due to the presence of different small quantities of impurity. EuPO 4 possesses a short T 1 of 210 ms being close to that of the paramagnetic GdPO 4 (460 ms) [21].…”
Section: Longitudinal Relaxation Timessupporting
confidence: 57%
“…Previous studies on solid solutions containing rare-earth elements have shown that finding similar NMR shifts is an evidence for the presence of a similar environment around the nucleus detected by NMR [50][51][52]. It should also be noted that the line broadening is more important for the Eu-rich solid solutions (Table I), as expected for solid solutions with higher paramagnetic cation content (structural local disorder and/or anisotropic bulk magnetic susceptibility effects) [14,15,21,49].…”
Section: B 31 P Mas Nmr Spectrasupporting
confidence: 51%
See 1 more Smart Citation
“…[17][18][19][20] Solid state NMR has been reported to be helpful for studying paramagnetic systems. [21][22][23][24][25][26] Especially, the distribution of paramagnetic dopants can be investigated by the spin-lattice relaxation time, [27][28][29][30] hyperfine shifts [31,32] and the line-broadening effect. [27,33,34] Homogeneous distributions of Tb 3 + and Eu 3 + were shown to be correlated to NMR line broadening and positively related to the brightness of phosphors.…”
Section: Articlesmentioning
confidence: 99%
“…20 In this contribution solid-state NMR is used to investigate co-doping heterogeneity. In case of a diamagnetic solid host with NMR-active nuclei solid-state NMR has been used to investigate the dopant distribution of a single kind of paramagnetic dopant (''mono-doped'') in different ways: spin-lattice T 1 relaxation, [21][22][23] line width [24][25][26] and visibility function (see below). 27,28 A T 1 -T 2 correlation map was also shown to be useful in studying a paramagnetic site distribution at the surface of porous materials.…”
Section: Introductionmentioning
confidence: 99%